Cu(II) complexes of N-rich aroylhydrazone: magnetism and catalytic activity towards microwave-assisted oxidation of xylenes - Sutradhar, Manas (2019)
The new aroylhydrazone N'-(di(pyridin-2-yl) methylene) pyrazine-2-carbohydrazide (HL) species, rich in N-donor sites, has been used to synthesize Cu(II) compounds with different nuclearities, viz. the binuclear [Cu2(mu-1.N3,2.N2O-L)(Cl) 3(MeOH)] (1), the octanuclear [Cu4(mu-1.N3,2.N2O-L) 2(mu-Cl) 3(Cl) 3] 2 (2) and the 1D coordination polymer [Cu3(mu 3-1.N3,2.N2O, 3.N-L)(mu-NO3)(NO3) 3(H2O) 3] n center dot nNO3 (3). They have been characterized by elemental analysis, FT-IR and single crystal X-ray diffraction. The magnetic properties of 2 and 3 have been explored using variable temperature magnetic measurements. The catalytic performances of the compounds were evaluated towards the peroxidative oxidation of o-, p-and m-xylenes under microwave irradiation, leading to the formation of the corresponding methyl benzyl alcohol, tolualdehyde and toluic acid as the major products. Complex 3 exhibits the best catalytic activity towards the oxidation of p-xylene with a total yield of 37% (4-methylbenzyl alcohol + p-tolualdehyde + p-toluic acid).